A Novel Danshensu Derivative Prevents Cardiac Dysfunction and Improves the Chemotherapeutic Efficacy of Doxorubicin in Breast Cancer Cells. Issue 1 (January 2016) - Wang, Liang; Zhang, Xiaojing; Chan, Judy Yuet‐Wa; Shan, Luchen; Cui, Guozhen; Cui, Qingbin; Wang, Yingfei; Li, Jingjing; Chen, Huanxian; Zhang, Qingwen; Yu, Pei; Han, Yifan; et al.
ABSTRACT: Doxorubicin (Dox) is an anthracycline antibiotic widely used in clinics as an anticancer agent. However, the use of Dox is limited by its cardiotoxicity. We have previously shown that a Danshensu (DSS) derivative, ADTM, displayed strong cardioprotective effects. With improved chemical stability and activity, a novel DSS derivative, D006, based on the structure of ADTM, was synthesized. In the present study, the protective effects of D006, indexed by attenuation of the cardiotoxicity induced by Dox as well as chemosensitizing effects that increase the antitumor activity of Dox, were investigated. Our results showed that D006 was more potent than either parental compound, or their use in combination, in ameliorating Dox‐induced toxicity in H9c2 cells. In our zebrafish model, D006, but not DSS, alone significantly preserved the ventricular function of zebrafish after Dox treatment. Moreover, D006 upregulated mitochondrial biogenesis and increased mtDNA copy number after Dox treatment of H9c2 cells. D006 promoted the expression of HO‐1 protein in a time‐dependent manner while the HO‐1 inhibitor, Znpp, reversed the protective effects of D006. In human breast tumor MCF‐7 cells, D006 enhanced Dox‐induced cytotoxicity by increasing apoptosis. In conclusion, our results indicate that a new DSS derivative exhibits promising protective effects against Dox‐induced cardiotoxicity both in vivo and in vitro, an effect at least partially mediated by induction of HO‐1 expression and the activation of mitochondrial biogenesis. Meanwhile, D006 also potentiated the anti‐cancer effects of Dox in breast tumor cells. J. Cell. Biochem. 117: 94–105, 2016. © 2015 Wiley Periodicals, Inc.